Johann Hermann Knoop en de kunst van de geschiedenis - Wagenaar, Cor (Bulletin KNOB, 2016)
Johann Hermann Knoop was born at the beginning of the eighteenth century in Freyenhagen near Kassel (Germany), where his father was in charge of the palace gardens. In 1731, Maria Louise, daughter of the Elector and widow of the Frisian stadholder Johan Willem Friso, summoned Knoop to the court of the ‘Frisian’ House of Orange in Leeuwarden. There he was responsible for the layout and maintenance of the gardens and estates. In 1747 the ‘Hollandse’ branch of the House of Orange died out and the Frisian branch relocated to The Hague. Leeuwarden lost its status as royal residence and not long afterwards Johann Hermann lost his position. So began his second career as scientist and publicist. Knoop regarded mathematics, and in particular geometry, as the key to understanding the natural world. It is significant that Knoop’s first publication, in 1744, was a revised and enlarged edition of J. Morgenster’s handbook for engineers and surveyors, Werkdadige Meetkonst. His next scientific publication brought him international fame. Knoop’s Pomologia appeared in Dutch in 1758; German and French translations followed in 1760 and 1771 respectively. Pomologia classifies all the then known apple and pear trees and their fruit, and is embellished with exceptionally fine, coloured drawings. It was followed by similar volumes on garden trees and fruit trees; the trilogy was reprinted several times. Knoop’s contributions to the Dutch encyclopedia underscores his status as a respected scientist. However, his greatest importance derives from the publications in which he addressed himself to the ordinary citizen. These can be divided into three categories: garden books, historical-anthropological works and, finally, publications in which he endeavoured to summarize information useful in everyday life. Knoop’s first book written for a general readership, published in 1752, was about the garden: De beknopte huishoudelyke hovenier, of korte verhandeling en synonymische en meernamige listen (The concise home gardener, or brief discourse and synonymic and multiname lists). It was followed in 1760 by a volume explaining the ornamental garden. A volume dealing with the medicinal use of plants completed the trilogy in 1762. Just as mathematics helps us to understand the natural world, so history and anthropology are helpful in understanding the social order. After a 1759 booklet about heraldry, geography and history in the form of a game (a precursor of today’s ‘serious gaming’), in 1763 Knoop published his masterwork in this field: Tegenwoordige staat of historische beschryvinge van Friesland (Current state or historical account of Friesland), a hefty 539-page work. The third category summarizes existing knowledge. In 1756 the first volume of Jongmans onderwijser appeared, followed three years later by volume two; together they amounted to over 1500 pages of information on mathematics, bookkeeping, the art of letter writing, the proper way to draw up contracts, geometry, stereometry, political history, logic, physics, mechanics, architecture, astronomy and instructions for making sundials. The section on architecture is over one hundred pages long and can lay claim to being the Netherlands’ best concealed eighteenth-century architectural treatise. Knoop’s world was that of science, art and popular education. He believed that it was science that determined the individual’s position in the natural and social order and he felt that it was essential that people should be aware of this: dissemination of knowledge was as important for him as scientific research, and that made him a typical representative of the Enlightenment.